PENGARUH STRATEGI PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR KEBUGARAN JASMANI PADA MATA PELAJARAN PJOK SISWA KELAS XII SMA N 4 SEMARANG: The Influence of Differentiated Learning Strategies on Physical Fitness Learning Outcomes in the Pjok Subject of Class XII Students Of SMA N 4 Semarang - Muhamad Afiful Umam; Setiyawan; Budi sulistiyanto (JSH: Journal of Sport and Health, 2024)
This research was based on the results of interviews during observations which concluded that there was a problem of less effective learning approaches in PJOK subjects on student learning outcomes. This research uses quantitative research. This research uses a pre-experimental type of experiment using a One – Group Pretest – Posttest design. Researchers used a sample of 1 class XII 7 SMA N 4 Semarang. The data collection technique in this research uses tests. Data analysis uses paired sample tests. The average value of the pre-test results for student learning outcomes was 85.28, while the average value of the post-test results for student learning outcomes was 89.50. This research concludes that differentiated learning has an influence on PJOK learning outcomes in physical fitness material. This can be supported by the results of the paired sample correlation test. The final result obtained was α = 0.000, thus α < 0.05.